Effort To Prevent Post Partum Depression : Scoping Review - Christiana, Indah (International Conference on Sustainable Health Promotion, 2023)
This study aims to review the research results on efforts taken to avoid the occurrence of postpartum depression. The review employs the PRISMA ScR framework, while articles are sourced through four databases: Pubmed, ScienceDirect, Wiley, and Google Scholar. The obtained data was analysed using Critical Appraisal at The Joanna Briggs Institute (JBI). Out of 3,509 pre-selected articles, only eight met the inclusion criteria. This review found several interventions that can be done to prevent postpartum depression, including educational videos about baby crying, progressive muscle relaxation, Spiritual Management of Relaxation Therapy (SMARTER), Moderate Physical Activity in an Aquatic Environment During Pregnancy (physical activity), Cognitive Behavior Therapy (CBT), effleurage method, and exercise and diet methods. Studies have demonstrated that these approaches effectively prevent or minimise postpartum depression.